Assessment of the Potential Role of Streptomyces in Cave Moonmilk Formation - Maciejewska, Marta; Adam, Delphine; Naômé, Aymeric; Martinet, Loïc; Tenconi, Elodie; Całusińska, Magdalena; Delfosse, Philippe; Hanikenne, Marc; Baurain, Denis; Compère, Philippe; Carnol, Monique; Barton, Hazel A.; et al. (Frontiers in Microbiology, 2017)
Moonmilk is a karstic speleothem mainly composed of fine calcium carbonate crystals (CaCO3) with different textures ranging from pasty to hard, in which the contribution of biotic rock-building processes is presumed to involve indigenous microorganisms. The real microbial input in the genesis of moonmilk is difficult to assess leading to controversial hypotheses explaining the origins and the mechanisms (biotic vs. abiotic) involved. In this work, we undertook a comprehensive approach in order to assess the potential role of filamentous bacteria, particularly a collection of moonmilk-originating Streptomyces, in the genesis of this speleothem. Scanning electron microscopy (SEM) confirmed that indigenous filamentous bacteria could indeed participate in moonmilk development by serving as nucleation sites for CaCO3 deposition. The metabolic activities involved in CaCO3 transformation were furthermore assessed in vitro among the collection of moonmilk Streptomyces, which revealed that peptides/amino acids ammonification, and to a lesser extend ureolysis, could be privileged metabolic pathways participating in carbonate precipitation by increasing the pH of the bacterial environment. Additionally, in silico search for the genes involved in biomineralization processes including ureolysis, dissimilatory nitrate reduction to ammonia, active calcium ion transport, and reversible hydration of CO2 allowed to identify genetic predispositions for carbonate precipitation in Streptomyces. Finally, their biomineralization abilities were confirmed by environmental SEM, which allowed to visualize the formation of abundant mineral deposits under laboratory conditions. Overall, our study provides novel evidences that filamentous Actinobacteria could be key protagonists in the genesis of moonmilk through a wide spectrum of biomineralization processes.